STEM-Project based Learning in Physics Concept of Measurement to Enhance High School Students' Scientific Literacy - Zaida Ilma, Arina; Utami, Estri; Kusumaningtyas, Dian Artha (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Students' scientific literacy in understanding physics concepts still needs to improve. This study aims to determine scientific literacy using STEM Project-based Learning (PjBL) in learning physics, especially measurement concepts. The study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, including planning, acting, observing, and reflecting. The subjects were students in the tenth grade of SMA Negeri 8 Yogyakarta for the 2023/2024 academic year, consisting of 33 students. The data collection techniques and instruments used a written test with three questions describing scientific literacy, observation, and documentation. STEM-PjBL through project activities carried out in two learning cycles. In the first cycle, the teacher implemented a project for making posters regarding measuring instrument specifications, while in the second cycle, there was a project for making miniature measuring instruments. After the first cycle, students' scientific literacy increased to 0.48 with a moderate category. In the second cycle, it increased to 0.68. Using STEM-PjBL is thought to have just a modest improvement. These results underline the potential of STEM-PjBL as a fundamental teaching tool to improve students' scientific literacy as they show how well it fosters a strong awareness of physics ideas. Future studies could examine the effects of STEM-PjBL on more scientific ideas or within varied educational environments.